IMPLEMENTASI SERTIFIKAT HALAL GRATIS (SEHATI) BAGI PELAKU UMKM DI DESA TONJONGSARI CIKALONG TASIKMALAYA - Muhamad Reza Atqia; Doni Ramdani, Imam Baehaqi, Agus Abdus Sahid (Adiba Aisha Amira, 2024)
The halalness of a product in the current era can determine the income and profits of a product being sold. In a business context, providing halal food and drinks can attract regular, responsive customers, not only Muslims but also non-Muslims. Through the SEHATI program created by the government through the Ministry of Religion, business actors benefit greatly, because it makes it easier to obtain halal certification for their products. This writing is motivated by the fact that there are still UMKM products in Tonjongsari Cikalong Tasikmalaya Village that have not been certified. The approach used is qualitative research with an observation survey method. Socialization and mentoring activities were carried out by the STIS As-Sa'adah Sukasari Sumedang KKN Team. The activities carried out go through four stages, namely: social reflection, participatory planning, program implementation and evaluation. As a result of this activity, fish cracker and banana chip products received halal certificates.